Fractais de Rauzy, autômatos e frações contínuas - Pavani, Gustavo Antonio [UNESP] (2015)
The aim of this doctoral thesis is to study some topological and arithmetical properties of a class of Rauzy fractals which do not have the (F) Property. In particular we proved that the Rauzy fractals of this class induce a periodic tiling of the complex plane. Furthermore, we studied the construction of a nite automaton able to generate the boundary of these fractals, and to parametrize them. This automaton is also used to establish conditions on the number of neighboors of these fractals. We also studied the best simultaneous diophantine approximation for pairs of algebraic numbers v = ( ; 2), where 1= is a cubic Pisot number whose conjugates are not real numbers, and 1= does not satisfy the (F) Property